EVALUATION OF A DIGITAL LIBRARY IN SUPPORTING STUDENTS’ INDEPENDENT LEARNING USING THE CIPP MODEL AT PEPABRI UNIVERSITY, MAKASSAR - Mutmainnah, Inayatul; Rasyid , Muhammad Nur Akbar; Mania, Sitti (Jurnal Kajian Pendidikan dan Psikologi, 2025)
Digital transformation in higher education requires the availability of adaptive learning facilities, including digital libraries that support students’ independent learning. This study aims to evaluate the development and implementation of a digital library in fostering independent learning at Pepabri University Makassar using the CIPP (Context, Input, Process, Product) evaluation model. In addition, the study assesses the effectiveness of system implementation in terms of student engagement and its integration into the learning process. A qualitative research approach was employed, with data collected through in-depth interviews, observations, and documentation involving students, lecturers, librarians, and academic managers. The findings reveal that, from the context dimension, the development of the digital library has not been based on a systematic analysis of user needs. From the input aspect, although infrastructure is available, it is not sufficiently supported by user competencies or integrative institutional policies. In the process dimension, the digital library has not been formally integrated into the curriculum or learning activities. From the product perspective, system utilization remains incidental and has not significantly enhanced students’ independent learning. Student engagement with the digital library is also relatively low due to limited guidance, training, and the absence of formal policies encouraging system integration into teaching practices. This study recommends conducting periodic needs assessments, strengthening digital literacy training, integrating digital libraries into course learning plans (RPS), and implementing continuous evaluation to improve system effectiveness. The findings contribute to strengthening digital library governance as a strategic instrument for independent learning in the digitalization era of higher education.